Transcranial direct current stimulation over the left anterior temporal lobe during memory retrieval differentially affects true and false recognition in the DRM task. (23rd June 2021) - Friehs, Maximilian A.; Greene, Ciara; Pastötter, Bernhard
Abstract: Transcranial direct current stimulation (tDCS) is a form of non‐invasive brain stimulation that has been used to modulate human brain activity and cognition. One area which has not yet been extensively explored using tDCS is the generation of false memories. In this study, we combined the Deese‐Roediger‐McDermott (DRM) task with stimulation of the left anterior temporal lobe (ATL) during retrieval. This area has been shown to be involved in semantic processing in general and retrieval of false memories in the DRM paradigm in particular. During stimulation, 0.7 mA were applied via a 9 cm² electrode over the left ATL, with the 35 cm² return electrode placed over the left deltoid. We contrasted the effects of cathodal, anodal, and sham stimulation, which were applied in the recognition phase of the experiment on a sample of 78 volunteers. Results showed impaired recognition of true memories after both anodal and cathodal stimulation in comparison to sham stimulation, suggesting a reduced signal‐to‐noise ratio. In addition, the results revealed enhanced false recognition of concept lure items during cathodal stimulation compared to anodal stimulation, indicating a polarity‐dependent impact of tDCS on false memories in the DRM task. The pathway by which tDCS modulated false recognition remains unclear: stimulation may have changed the activation of irrelevant lures or affected the weighting and monitoring of lure activations. Nevertheless, these results are a first step towards using brain stimulation to decrease false memories. Practical implications of the findings for real‐life settings, for example, in the courtroom, need to be addressed in future work. Abstract : The Deese‐Roediger‐McDermott paradigm is a reliable way to produce false, illusory memories. Transcranial direct current stimulation (tDCS) was applied over the left anterior temporal lobe to modulate semantic processing. Both anodal and cathodal tDCS during the recognition phase impaired recognition of true memories, which suggests a reduced signal‐to‐noise ratio. Cathodal tDCS increased false recognition of concept lure items, while anodal tDCS reduced false recognition compared to sham stimulation.